THE EFFECT OF SO42- SULPHATE ANIONS ON THE ULTRAFINE TITANIA NUCLEATION - V. O. Kotsyubynsky; I. F. Myronyuk; B. K. Ostafiychuk; V. L. Chelyadyn; A. B. Hrubiak; I. I. Hryhoruk (Vasyl Stefanyk Precarpathian National University, 2016)
We have proposed and experimentally tested a phenomenological model of SO42- sulphate anions effect on the titania nucleation during hydrolysis of titanium tetrachloride. Sulphate anions form the chelating bidentate complexes with primary [Ti(OH)h(OH2)6-h](4-h)+ with the influence on the next olation process and promotion of anatase phase nucleation.